Phytoconstituents of Butterbur (P. japonicus), their metabolic pathway and ability to modulate bone morphogenic protein (BMP) signaling. Issue 1 (31st December 2023) - Belal, Amany; Ibrahim, Mona H.; Mahdi, Wael A.; Alshehri, Sultan; Ebrahim, Hasnaa Ali; Ghoneim, Mohammed M.; El-Sherbiny, Mohamed; Mehany, Ahmed B. M.; Ghamry, Heba I.
ABSTRACT: A library of natural sesquiterpene and phenolic compounds from Petasites japonicus are being investigated through different computational techniques to study their ability to target BMP. Lipinski rule, ADMET, molecular docking studies and metabolism were used to reach promising candidates with proposed activity against BMP. Four sesquiterpenes (kablicin, petisinol, bakkenolide D and bakkenolide IIIa) and four phenolic compounds exhibited drug-like properties (caffeic acid, petasiphenol, petasitesin A and petasitesin B), so they deserve further clinical exploration as bone loss modulators. The phenolic compounds specially fukinolic acid and petasiphenol showed lower binding energy with both BMPRIA and BMPRII than Icariin agonist and sesquiterpenes. Bakkenolide IIIa showed dual potential on both BMPRIA and BMPRII with binding energies equal – 7.82 and – 9.9 Kcal/mol respectively, which is more better score than Betulinic acid agonist. This research is focusing on plant-human interactions and exploring the ability of plant constituents to modulate a human protein such as BMP.